Experimental Salmonella gallinarum infection in light laying hen lines - Berchieri Jr., Angelo [UNESP]; De Oliveira, Gláucia Helaine [UNESP]; Pinheiro, Lucas Augusto Soeiro [UNESP]; Barrow, Paul A. (My University, 2000)
Although the epidemiology of fowl typhoid in chickens supposedly involves a vertical transmission stage, a previous work run by the authors has suggested that this did not happen in a commercial line of laying hens highly susceptible to systemic disease with Salmonella Gallinarum. A new experiment was carried out in two other lines of commercial layers, considerably more resistant than those used in the previous study. Clinical fowl typhoid was not observed, but Salmonella Gallinarum was isolated from the spleen and liver four weeks after infection and, sporadically, from the ovary.
Keywords: Infection; Laying hens; Salmonella Gallinarum; White Leghorn